PRINCIPLES OF LEGAL SUPPORT OF ENTREPRENEURIAL ACTIVITIES IN UKRAINE (Bulletin of criminological association of Ukraine, 2023)
In the article, the foundational principles defining legal support for entrepreneurial activity in Ukraine, as well as serving as vectors for the development of corresponding social relations, were examined. A scientific classification of the principles of legal support for entrepreneurial activity in Ukraine based on their scope of application was carried out, allowing for a deeper understanding of the essence and specifics of this important category. It was emphasized that classification of principles, as an important scientific research method, not only systematizes knowledge about research objects but also identifies their key characteristics and most significant aspects of functioning. This contributes to a better understanding of administrative and legal support for entrepreneurial activity and its development as the basis for Ukraine's national welfare. Three groups of principles were distinguished and characterized: general, interdisciplinary, and specific. It was established that general principles, such as the rule of law, legality, equality, transparency, and openness, are fundamental to all areas of law and provide a proper foundation for the functioning of legal systems. It was noted that interdisciplinary principles, including confidentiality, professionalism, dynamism, comprehensiveness, and independence, define important aspects of legal practice related to the functioning of various areas of social relations. It was highlighted that specific principles focus on particular aspects of legal support for entrepreneurial activity, including proactivity, client orientation, conflict of interest prevention, ethical conduct, and integrity. The necessity of a thorough analysis of the normative nature of these principles was emphasized, as their legal enshrinement is crucial for ensuring the effectiveness of legal support.
Keywords: legal support; entrepreneurial activity; administrative-legal regulation; principles; general principles; interdisciplinary principles; specific principles